Magic numbers and growth sequences of small face-centred-cubic and decahedral clusters - Doye, J; Wales, D (1995)
Growth sequences for small decahedral and face-centred-cubic (fcc) clusters are predicted by maximisation of the number of nearest-neighbour contacts. These sequences allow us to deduce likely magic numbers for fcc and decahedral clusters which may be appropriate to neutral clusters of C60 molecules. © 1995.